Analisis Kegagalan Komponen Overhead Crane dengan Metode Failure Mode and Effect Analysis (FMEA) - Virdana Adwa Metdifa Husna; Dian Asa Utari; Aulia Nadia Rachmat (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Repair and maintenance activities aim to increase the functional capability of a system or tool used in production. At PT. Lintech Duta Pratama (PT. LDP), overhead crane is used as a means of moving materials and finished goods. This tool operates to transport materials and finished goods continuously for ± 7 hours per day for 5 working days a week. However, maintenance actions have not been carried out optimally due to a lack of manpower/workers. Thus resulting in delays in the implementation of maintenance activities and affect the completion of production. Against this background, failure identification was carried out using the Failure Mode and Effect Analysis (FMEA) method on the 12.5T overhead crane. With this method the results obtained by filling in the FMEA Worksheet showed that there were 13 components that had the highest risk level value, with 26 failure modes from whole component. The highest RPN value is for the MCB/main power supply component with a value of 209, while the lowest is for the hoisting hook component with a value of 7. So that this component can be considered by the maintenance team and related parties in the company when carrying out maintenance activities on the overhead crane equipment